Educational Inequality by Race in Brazil, 1982–2007: Structural Changes and Shifts in Racial Classification - Marteleto, Leticia J. (2012)
Despite overwhelming improvements in educational levels and opportunity during the past three decades, educational disadvantages associated with race still persist in Brazil. Using the nationally representative Pesquisa Nacional de Amostra por Domicílio (PNAD) data from 1982 and 1987 to 2007, this study investigates educational inequalities between white, pardo (mixed-race), and black Brazilians over the 25-year period. Although the educational advantage of whites persisted during this period, I find that the significance of race as it relates to education changed. By 2007, those identified as blacks and pardos became more similar in their schooling levels, whereas in the past, blacks had greater disadvantages. I test two possible explanations for this shift: structural changes and shifts in racial classification. I find evidence for both. I discuss the findings in light of the recent race-based affirmative action policies being implemented in Brazilian universities.